The Effect of Frailty on Body Composition and Its Impact on the Use of SGLT-2 Inhibitors and GLP-1RA in Older Persons with Diabetes - Alan Sinclair; Izel Siqueira; Ahmed Abdelhafiz (Metabolites)
The association of frailty with body composition is complex. Frailty can be associated with significant anorexia and weight loss or overweight and obesity. In addition, the development of frailty leads to changes in muscle mass, muscle fibre type, and visceral fat. In older people with diabetes, frailty-induced body composition changes are clinically relevant as they may affect the metabolic profile of the frail person. The determinants of insulin resistance in frail older persons with diabetes include factors such as total body weight and the ratio of lean muscle mass to visceral fat mass. The predominant loss of insulin-resistant skeletal muscle fibres type II, in comparison to insulin-sensitive type I fibres, is another factor that modifies the overall insulin resistance of the individual. As a result, frailty appears to be a heterogeneous condition with variable insulin resistance across a metabolic spectrum. The spectrum spans from a sarcopenic obese frail phenotype at one end to an anorexic malnourished frail phenotype at the other end. The introduction of SGLT-2 inhibitors and GLP-1RA with novel anti-metabolic syndrome properties, not just glucose-lowering effect, should influence clinicians’ choice in frail older persons with diabetes. These agents are likely to be beneficial in patients at the sarcopenic obese end of the frailty spectrum, who should benefit most due to their high baseline risk of progression of metabolic syndrome, high insulin resistance, and the increased prevalence of cardiovascular risk factors. On the other hand, patients at the anorexic malnourished end of the frailty spectrum are likely not suitable for such therapy due to the regression of metabolic syndrome in this group of patients and the increased risk of further weight loss, dehydration, and hypotension.